2021
DOI: 10.1097/mnm.0000000000001423
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of LV diastolic dysfunction in myocardial perfusion imaging: a correlative study with transthoracic echocardiography

Abstract: Objective Myocardial perfusion imaging (MPI) by gated single-photon emission computed tomography (SPECT) is a feasible method in the evaluation of left ventricular perfusion and function. The purpose of this study was to determine the threshold and grading of left ventricular (LV) diastolic dysfunction (LVDD) using gated SPECT MPI. Methods A total of 149 patients were recruited in the study. All of the patients underwent a standard 2-day stress/rest gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Yamano et al [ 20 ] compared LV diastolic function parameters measured by gated single-photon emission tomography with colour Doppler ultrasound, suggesting a moderate correlation between PFR and E, a significant correlation with E/e’ ratio. Malek et al [ 21 ] showed that myocardial perfusion imaging can be used as a highly specific means of detecting LV diastolic dysfunction compared with echocardiography. In the present study, we applied a correlation analysis between diastolic functional parameters obtained by planar MUGA and the average E/e’ ratio, showing that there was some correlation between PFR, TPF, PFR combined with TPF, and the average E/e’ ratio, but the correlation coefficients obtained in this study were small and larger sample size is needed of studies for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Yamano et al [ 20 ] compared LV diastolic function parameters measured by gated single-photon emission tomography with colour Doppler ultrasound, suggesting a moderate correlation between PFR and E, a significant correlation with E/e’ ratio. Malek et al [ 21 ] showed that myocardial perfusion imaging can be used as a highly specific means of detecting LV diastolic dysfunction compared with echocardiography. In the present study, we applied a correlation analysis between diastolic functional parameters obtained by planar MUGA and the average E/e’ ratio, showing that there was some correlation between PFR, TPF, PFR combined with TPF, and the average E/e’ ratio, but the correlation coefficients obtained in this study were small and larger sample size is needed of studies for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the PFR showed the most significant correlation with the other functional parameters of G-SPECT MPI. Although the correlation of G-SPECT with other echocardiographic and angiographic techniques for evaluating diastolic function is acceptable [21], there are also reports of lower sensitivity of G-SPECT MPI [22,23]. However, it seems that the lower sensitivity of G-SPECT MPI is most commonly related to the detection of more advanced stages of diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular diastolic dysfunction often precedes systolic dysfunction. Thus, even in asymptomatic patients, the evaluation of diastolic function is of great significance for patient prognosis and treatment strategies ( 26 ). There were no significant differences in the LVEF, EDV, ESV, and FV between the experimental group and the control group (P>0.05), indicating that there were no differences in left ventricular systolic function between the patients with HF and the normal controls.…”
Section: Discussionmentioning
confidence: 99%